Reliability evaluation and multi-objective optimization of combustion chamber’s key components of marine engine - Lei Hu; Wentong Wang; Xu Wang; Jianguo Yang; Yonghua Yu; Chunyang Mei (Case Studies in Thermal Engineering)
Combustion chamber’s key components of marine engine exhibit varied reliability evaluation indicators, and conventional methodologies fail to account for performance degradation of specific evaluation index because of reliability with coupling and cross-dependencies among different components, consequently rendering existing reliability optimization inadequate for application requirements. Through establishing thermo-mechanical coupling simulations and creep-fatigue life method, the thermal-load characteristics and life indices of key components are systematically analyzed. Response surface methodology is used to establish reliability prediction models under sensitive factors of fuel injection, valve, and cooling systems, and a reliability comprehensive evaluation method based on entropy weight and grey correlation methods has been proposed. Constrained multi-objective optimization of reliability is conducted through contrastive analysis of different optimization algorithms. The research shows that the multi-objective particle swarm optimization algorithm achieves the best performance, the maximum temperatures of the piston, cylinder head, and liner decrease by 3.90 %, 5.66 %, and 6.52 %, the maximum thermo-mechanical coupling stresses reduced by 9.41 %, 7.83 %, and 4.97 % respectively, and creep-fatigue life enhancements reach 3.84 % and 12.67 % for the piston and cylinder head. The study establishes an effective method for reliability optimization of combustion chamber’s key components and presents significant engineering applications for reliability improvement for marine engines.